Pengaruh Gaya Hidup Hedonisme, Prilaku Konsumtif dan Pentingnya Literasi Keuangan terhadap Pengelolaan Keuangan Pribadi Mahasiswa Asrama Asmadewa Yogyakarta - Yosefa Renan Panu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to examine and analyze the influence of a hedonistic lifestyle, consumptive behavior and the importance of literacy on student personal financial management. The population used in this study were Asmadewa Jogja hostel students, totaling 100 people and 53 sample respondents who were determined using Non-Probability Sampling. Based on the test results and analysis in this study, it can be concluded that the hedonistic lifestyle and consumptive behavior have a positive effect on student personal financial management. Meanwhile, Financial Literacy has no effect on Student Personal Financial Management.